RAISING THE DURABILLITY CURVES IN CASE OF WELDING ELEMENTS - Claudiu BABIS; Oana CHIVU; Zoia APOSTOLESCU; Catalin AMZA (Fiabilitate şi Durabilitate)
Raising the durabillity curves is very important, being a useful tool in assessing the duration of the fatigue life of an item or welded structure. Determination of life duration up to fail, indicate us the right time for the rehabilitation of welded structure leading to labor savings and avoiding catastrophic failurewe that would endanger people's lives. The paper will present for three welded specimens experimental determinations of variable load cycles until failure, then will rise durabillity curves using a mathematical program.